Response for Forum in Cambridge Journal of Postcolonial Literary Inquiry. (September 2019) - Appadurai, Arjun
Abstract : I am grateful for the responses to my essay on "repeat viewing" by Kabir, Mazumdar, and Wong, each of whom offers a sympathetic critical response, pointing to ways of elaborating and complicating my argument about the relationship of repetition to difference in Bollywood films. In this comment I stress issues of genre, history, and context.